2014
DOI: 10.1016/j.molcel.2014.06.027
|View full text |Cite
|
Sign up to set email alerts
|

SWR1 and INO80 Chromatin Remodelers Contribute to DNA Double-Strand Break Perinuclear Anchorage Site Choice

Abstract: Persistent DNA double-strand breaks (DSBs) are recruited to the nuclear periphery in budding yeast. Both the Nup84 pore subcomplex and Mps3, an inner nuclear membrane (INM) SUN domain protein, have been implicated in DSB binding. It was unclear what, if anything, distinguishes the two potential sites of repair. Here, we characterize and distinguish the two binding sites. First, DSB-pore interaction occurs independently of cell-cycle phase and requires neither the chromatin remodeler INO80 nor recombinase Rad51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
215
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(228 citation statements)
references
References 58 publications
(136 reference statements)
10
215
2
1
Order By: Relevance
“…In yeast, persistent DSBs contain H2A.Z and are relocated to the nuclear membrane by a mechanism requiring H2A.Z-remodeling ATPases (49,50). Further, DSBs tethered to the nuclear lamina can be repaired by the alt-NHEJ pathway (51).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, persistent DSBs contain H2A.Z and are relocated to the nuclear membrane by a mechanism requiring H2A.Z-remodeling ATPases (49,50). Further, DSBs tethered to the nuclear lamina can be repaired by the alt-NHEJ pathway (51).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the DNA damage response mediator Rad9 (53BP1 in mammals) and Swr1-dependent Htz1 (also known as H2A.Z) incorporation were previously reported to promote DSB mobility 15 . Indeed, we found that subtelomeric DSB repair was greatly dependent on Rad9 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4e,f). DSBs relocating closer to the nuclear envelope often exhibit increased physical interactions with the Mps3 inner nuclear membrane protein 13,15 . Indeed, anti-Mps3 ChIP analysis showed that subtelomeric DSB-Mps3 interaction levels are increased in cells lacking Lrs4 or Cik1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To observe the chromatin dynamics around the double strand break (DSB), lacO/LacI-EGFP was combined with a DSB induction system using an endonuclease, the I-SceI system, in mouse NIH2/4 cells and S. cerevisiae (Soutoglou et al 2007, Dion et al 2012, Mine-Hattab and Rothstein 2012. They showed that the chromatin mobility around DSB was higher than the control and the chromatin around DSB moved to the subnuclear region near the T. Hirakawa and S. Matsunaga Cytologia 81(2) nuclear envelope (Horigome et al 2014). Moreover, chromosome translocation was monitored by the combination system in mouse NIH3T3 cells (Roukos et al 2013).…”
mentioning
confidence: 99%